Diagnostic Problem in a Patient with Tuberculosis Arthritis - Dicky Febrianto; Awalia Awalia (Current Internal Medicine Research and Practice Surabaya Journal, 2023)
Extra-pulmonary tuberculosis (TB) remains a big public health problem worldwide. Although TB most commonly affects the lungs, any organ or tissue can be involved. TB arthritis is a rare form of extra-pulmonary TB. TB arthritis usually manifests as mild and non-specific arthritis. A 35-year-old male was admitted to the emergency room of Dr. Soetomo General Academic Hospital Surabaya due to pain of left knee since two days prior to admission. His symptom began on previous six months with the swelling of the left knee that gradually worsened so that he had an antalgic gait. Radiological examination of left knee joint showed inflammatory arthritis, accompanied by joint effusion and soft tissue swelling. USG examination of the left knee showed the presence of non-specific left knee arthritis. Patient underwent debridement. Anatomical pathology examination of the tissue obtained at the time of debridement, showed the TB granulomatous inflammation. The Ziehl-Nielson stain of left knee tissue also showed the TB granulomatous inflammation. Patient was then treated with analgesics and anti-TB drugs. The intensive phase of anti-TB therapy was planned to be 2 month, then evaluated and followed by continuation phase for about 7 months. The knee joint is the third most common site of osteoarticular TB after spine and hip. Insidious onset of pain which, in some patients may be present for years, is the usual presentation. The joint is usually warm, and wasting of the thigh muscles is usually marked. Synovial hypertrophy and effusion are present in most patients. The gold standard for diagnosis of TB arthritis is synovial biopsy, with positive results in 80% of cases. It shows caseating granulomas, lymphocytes, and giant cells with caseation, which are characteristics of TB arthritis. Synovial biopsy is generally recommended in any arthritis where clinical evaluation and routine investigations do not give a clear diagnosis.